2020
DOI: 10.1186/s13287-020-1562-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from bone marrow mesenchymal stem cells enhance fracture healing through the promotion of osteogenesis and angiogenesis in a rat model of nonunion

Abstract: Background: As important players in cell-to-cell communication, exosomes (exo) are believed to play a similar role in promoting fracture healing. This study investigated whether exosomes derived from bone marrow mesenchymal stem cells (BMMSC-Exos) could improve fracture healing of nonunion. Methods: BMMSC-Exos were isolated and transplanted into the fracture site in a rat model of femoral nonunion (Exo group) every week. Moreover, equal volumes of phosphate-buffered saline (PBS) and exosome-depleted conditione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
193
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(197 citation statements)
references
References 50 publications
2
193
1
1
Order By: Relevance
“…93 Similarly, BMSC-derived exosomes can enhance osteogenesis and angiogenesis partially through the BMP-2/Smad1/RUNX2 and HIF-1alpha/VEGF pathways at fracture sites to accelerate fracture repair in a femoral nonunion rat model. 94 Moreover, umbilical cord MSC-derived exosomes also promote fracture healing in a rat model of stabilized fracture, which is involved in the HIF-1alpha-mediated regulation of angiogenesis. 95 In addition to osteoporosis and fracture, an increasing number of studies have revealed that exosomes are closely involved in OA pathology and have strong therapeutic potential for this disease.…”
Section: Exosomementioning
confidence: 99%
See 1 more Smart Citation
“…93 Similarly, BMSC-derived exosomes can enhance osteogenesis and angiogenesis partially through the BMP-2/Smad1/RUNX2 and HIF-1alpha/VEGF pathways at fracture sites to accelerate fracture repair in a femoral nonunion rat model. 94 Moreover, umbilical cord MSC-derived exosomes also promote fracture healing in a rat model of stabilized fracture, which is involved in the HIF-1alpha-mediated regulation of angiogenesis. 95 In addition to osteoporosis and fracture, an increasing number of studies have revealed that exosomes are closely involved in OA pathology and have strong therapeutic potential for this disease.…”
Section: Exosomementioning
confidence: 99%
“…171,172 Moreover, BMSCderived exosomes can regulate a variety of physiological and pathological processes, including the immune response, osteogenesis, fibrosis, and angiogenesis. 94,[173][174][175] Several studies have reported that BMSC-derived exosomes significantly promote the regeneration and repair of injured tissues, including cartilage and subchondral bone. 174,[176][177][178][179][180][181] The exosomes as well as MVs/ microparticles (MPs) from TGFβ3-pretreated BMSCs significantly increased the expression of anabolic markers and decreased the levels of catabolic marker genes in osteoarthritic chondrocytes.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…Increasingly, MSC exosomes have replicated the wide-ranging therapeutic efficacies of MSCs in several injury and disease indications such as myocardial ischemia reperfusion injury [ 29 ], drug-induced liver injury [ 30 ], retinal laser injury [ 31 ], pulmonary hypertension [ 32 ], and graft-versus-host-disease [ 33 , 34 ]. MSC exosomes were also reported to be efficacious in enhancing skeletal muscle regeneration [ 35 , 36 ] ​and more recently cartilage [ 23 , [37] , [38] , [39] , [40] ] and bone regeneration [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies have shown that multiple regulatory factors and complex signaling pathways involved in the process of osteogenesis differentiation are regulated by MSC-exosomes. Specific pathways including Wnt, BMP, PI3K/Akt, insulin, TGFβ, and calcium signaling pathways may be affected by MSC-exosomes ( Cooper et al, 2019 ; Wei et al, 2019 ; Zhang et al, 2020 ). In aggregate, these researches demonstrate that MSC-exosomes carry much information that impacts key gene activation for osteogenesis including SATB2, Runx2, Dlx5, and Osterix (Osx; Fang et al, 2015 ; Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%